The genome of broomcorn millet - Zou, Changsong; Li, Leiting; Miki, Daisuke; Li, Delin; Tang, Qiming; Xiao, Lihong; Rajput, Santosh; Deng, Ping; Peng, Li; Jia, Wei; Huang, Ru; Zhang, Meiling; et al. (Nature communications, 2019)
Broomcorn millet ( Panicum miliaceum L.) is the most water-efficient cereal and one of the earliest domesticated plants. Here we report its high-quality, chromosome-scale genome assembly using a combination of short-read sequencing, single-molecule real-time sequencing, Hi-C, and a high-density genetic map. Phylogenetic analyses reveal two sets of homologous chromosomes that may have merged ~5.6 million years ago, both of which exhibit strong synteny with other grass species. Broomcorn millet contains 55,930 protein-coding genes and 339 microRNA genes. We find Paniceae-specific expansion in several subfamilies of the BTB (broad complex/tramtrack/bric-a-brac) subunit of ubiquitin E3 ligases, suggesting enhanced regulation of protein dynamics may have contributed to the evolution of broomcorn millet. In addition, we identify the coexistence of all three C 4 subtypes of carbon fixation candidate genes. The genome sequence is a valuable resource for breeders and will provide the foundation for studying the exceptional stress tolerance as well as C 4 biology. Broomcorn millet is one of the earliest domesticated plants and has the highest water use efficiency among cereals. Here, the authors report its genome assembly and annotation, which provides a valuable resource for breeders and paves the way for studying plant drought tolerance and C 4 photosynthesis.